Dealing with Difficult Emotions: Anger at the Truth and Reconciliation Commission of Canada - Reynaud, Anne-Marie (Anthropologica, 2014)
This article approaches the Canadian TRC and its aspiration for reconciliation from an emotions perspective, thereby acknowledging the significant role emotions play in constituting identities and political communities, as well as understanding emotions as central to how conflicts are generated, viewed and solved (Hutchison and Bleiker 2008). I explore Michael Ure’s claim that TRCs are host to a fundamental tension between the competing imperatives of justice (and its prime emotion of anger) and reconciliation (2008:286). The aim is to understand how survivors deal with this emotionally tense process and make sense of the TRC in this context.